880Dietary inflammatory index and the risk of adult depression symptoms. (2nd September 2021) - Shakya, Prem; Melaku, Yohannes Adama; Page, Amanda J; Adams, Robert J; Shivappa, Nitin; Hébert, James R; Gill, Tiffany K
Abstract: Background: The link between diet, inflammation and depressive symptoms (DepS) are of increasing interest. The study aims to assess the association between the dietary inflammatory index (DII ® ) and DepS using the North-West Adelaide Health Study (NWAHS) cohort and update the previous meta-analysis. Methods: A total of 1743 (mean□SD age 56.6±13.6 years, 51% female) and 859 (mean□SD age 58.4±12.1 years, 52.6% female) of NWAHS participants were included for cross-sectional and longitudinal analysis respectively. DII was determined using food frequency questionnaires, and the Center for Epidemiologic Studies Depression Scale (CES-D) assessed DepS. Log- and negative binomial regression were used to assess the association between quartiles of DII and DepS. Results: In a fully adjusted model, higher DII score (i.e. pro-inflammatory diet) was associated with 79% increase in odds of reporting DepS (ORQuartile4vs1 :1.79; 95% CI: 1.14-2.81; p trend =0.026). Men with higher DII had two-fold higher odds of DepS (ORQuartile4vs1 :2.27; 95% CI: 1.02-5.06; p trend =0.089). Women with higher DII had an 81% increase in odds of DepS (ORQuartile4vs1 :1.81; 95% CI: 1.01-3.26; p trend =0.068). These associations were consistent in the longitudinal analysis. The meta-analysis (n = 12) showed that a pro-inflammatory diet was associated with a 45% increase in odds of having DepS (ORQuartile4vs1 :1.45; 95% CI: 1.20, 1.74, p-value<0.01). Conclusions: A pro-inflammatory diet was positively associated with increased risk of DepS. Our findings support the current evidence that shows the role of pro-inflammatory diet in DepS. Key messages: Increase the consumption of anti-inflammatory diet to reduce depressive symptoms